MINAT MAHASISWA TERHADAP MATA KULIAH METODE NUMERIK DENGAN IMPLEMENTASI MEDIA TUTORIAL - Nora Surmilasari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Abstract— This study aims to determine the relationship of students with courses. This research was conducted at Universitas PGRI Palembang on mathematics education sixth semester students in academic year 2016-2017. This research is a qualitative research. Questionnaire data were analyzed descriptively and obtained conclusion. Has a high technique to the course of Numerical method by applying video tutorial in the course.Keywords— video tutorials, numerical methods, interests